Laurenti divo: Faunus, Pan and Silvanus in Virgil’s Aeneid - Lee Michael Fratantuono (Synthesis (La Plata), 2020)
Virgil employs various rural deities in his Aeneid as a means to explicate how the conflicted relationship between Aeneas’ Troy and Turnus’ Italy will be reconciled in the future Rome.